Developmental fitness curves: assessing sprint acceleration relative to age and maturity status in elite junior tennis players. (18th May 2020) - Myburgh, Gillian K.; Cumming, Sean P.; Coelho-e-Silva, Manuel; Malina, Robert M.
Abstract: Background: The influence of maturity-status on athletic performance is reasonably well-documented. Methodological and practical issues of assessment and lack of longitudinal data have impacted the success of various models. Aim: To develop age- and sex-specific developmental curves for sprint acceleration in elite youth tennis players and to address variation in performance relative to chronological and biological age. Subjects and methods: Measures of acceleration were available for 3120 elite youth tennis players aged 8–15 years attending National and Regional Talent Identification days. Variation in acceleration by chronological and estimated biological ages was evaluated in corresponding data for an independent sample of elite youth players 8.9 to 15.1 years of age. Results: Acceleration varied as a function of chronological and biological age relative to developmental curves. Early maturing males and females had significantly poorer performances when acceleration was considered relative to biological age. Significant discrepancy in percentiles relative to biological versus chronological ages was also evident between early and late maturing players of each sex. Conclusion: Evaluating performance relative to developmental curves and maturity status may be a practical means of monitoring long-term athlete development in tennis.